Associations between socio-demographics, nutrition knowledge, nutrition competencies and attitudes in community-dwelling healthy older adults in Singapore: findings from the SHIELD study - Rebecca Hui San Ong; Wai Leng Chow; Magdalin Cheong; Gladys Huiyun Lim; Weiyi Xie; Geraldine Baggs; Dieu Thi Thu Huynh; Hong Choon Oh; Choon How How; Ngiap-Chuan Tan; Siew Ling Tey; Samuel Teong Huang Chew (BMC, 2021)
Abstract Background Nutrition literacy refers to an individual's knowledge, motivation and competencies to access, process and understand nutrition information to make nutrition-related decisions. It is known to influence dietary habits of individuals including older adults. This cross-sectional study was designed to: (1) understand the nutrition knowledge, competencies and attitudes of community-dwelling older adults in Singapore, (2) examine the differences between their nutrition knowledge, and socio-demographic factors, competencies and attitudes and (3) identify factors associated with better nutrition knowledge in older healthy adults in Singapore. Methods A total of 400 (183 males and 217 females) nourished community-dwelling older adults aged 65 years and above took part in this study. Malnutrition Universal Screening Tool (MUST) was used to determine individuals who were at low risk of undernutrition. Nutrition knowledge, competencies, attitudes and sources of nutrition information were measured using a locally developed scale. Nutrition knowledge scores were summed to form the nutrition knowledge index (NKI). Associations between NKI, competencies, attitudes and socio-demographic variables were examined using Chi-square and Fisher's exact tests. Factors associated with NKI were determined using a stepwise regression model with resampling-based methods for model averaging. Results Bivariate analyses found significant differences in NKI scores for gender, monthly household earnings, type of housing, the self-reported ability to seek and understand nutrition information and having access to help from family/friends. Females had higher NKI scores compared to males (p < 0.001). Compared to females, more males left food decisions to others (p < 0.001), and fewer males reported consuming home-cooked food (p = 0.016). Differences in educational level were found for competencies like the self-reported ability to seek (p < 0.001) and verify nutrition information (p < 0.001). Stepwise regression analysis showed that being female, Chinese, self-reported ability to understand nutrition information and having access to help from family/friends were associated with higher NKI scores. Conclusions Our study revealed that nutrition knowledge of older males in Singapore was lower than females and more left food decisions to others. Nutrition education programs could be targeted at both the older male, their caregivers and minority ethnic groups. Trial Registration This study was registered on 7 August 2017 at clinicaltrials.gov (ref. NCT03240952).